Karakteristik Lampu Hemat Energi Ditinjau dari Pengaruh Suplai Tegangan Listrik - Sabar Setiawidayat; Wahyu Sriyanto (Teknik Elektro Fakultas Teknik Universitas Widyagama Malang, 2022)
The circulation of Energy Saving Lamps or Self-Based Lamps in Indonesia, which promises the shape of lamps, variations in lamp power, lamp life, comparison of offered lamp brightness, low power absorption with brighter light, has caused many people to switch from using tube lamps and incandescent lamps to other types of lamps. this lamp. Indonesian Government regulation that requires LHE lamp manufacturers to include the Indonesian National Standard label as proof that the lamp is within the specified Efficacy limit. General Regulation of Electrical Installation and PT. PLN urges its consumers that electricity users can maintain the load power factor of not less than 0.8. This study aims to determine the amount of current consumption and electrical power required by LHE lamps labeled with SNI from the Panasonic, Shinyoku and ACR brands which were obtained randomly in the market. 10 lamps 18 watts, 220 volts as a sample, given a variation of the supply voltage between 110 volts to 240 volts with 10 volt steps. The results showed that the average real power at a voltage of 220 volts was in accordance with the labels on all brands. All three lamp brands have a power factor below 0.5. Characteristics of voltage to real power for Panasonic LHE obtained y = -0.0226x2 + 8.889x - 673.88, LHE Shinyoku y = -0.0002x2 + 0.3184x + 109.22, and LHE ACR y = -0.0003x2 + 0.2852x + 120.91